Private Telecom Projects : Private Activity Down 15 Percent in 2003 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Drawing on the World Bank's private participation in infrastructure project database, this note reviews developments in the telecommunications sector in 2003. Data for the year show that investment in projects with private participation was back to 1996 levels. Two regions -the Middle East and North Africa and Europe and Central Asia-saw private activity grow in 2003. And developing country companies were the most active sponsors. Private activity in telecommunications in low and middle-income countries remained subdued in 2003. Investment flows to projects with private participation declined for the third consecutive year, amounting to US$28.5 billion. Nevertheless, 22 new projects with fixed or mobile operators reached financial closure in 16 developing countries. Most of the decline in investment occurred in lower-middle-income countries, where investment flows dropped from US$11.3 billion to US$8.8 billion. Low-income countries also contributed to the slowdown, with investment flows falling from US$6.8 billion to US$5.4 billion. Flows were nevertheless strong, the fourth highest for this group in 1990-2003. Investment flows to upper-middle-income countries grew by 9 percent to US$14.2 billion, yet were still close to the level of 1996.